(3HjGf eYGfj GdMQha GdLGQIs
(3ChdgG (B:s
(3CeG (B"(3pef(B" (3adgG eYGmf GdChd GdJHYjV fMh(B: "(3MJi JfabhG eeG JMHhf(B" s
(3BNQgG (B:s
(3bjd dHYVge cja CUHMJ, bGd cNjQ, Cj Ydi NjQ hgh bdjd hGSJYed GSekG HeYfi eKd JeJ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B41 - (3U(B49s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B52 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI (B- (3OeTb (B(9304) s
Keywords: (3GdfMhs